Existing Before God : Soren Kierkegaard and the Human Venture - Sponheim, Paul R. (Mapping the tradition., 2017)
Existing Before God introduces readers to one of the most important 19th century Christian thinkers, Soren Kierkegaard. In this volume, Paul R. Sponheim, unfolds Kierkegaard's Sickness unto Death- a key text outlining the problem of the human condition and the paradoxical heart of authentic Christian faith, the qualitative difference between God and creatures and its synthesis in the God-man. Sponheim also draws out the connections between this text and Kierkegaard's larger theological and ethical vision, and the reception and significance of this text in the modern and contemporary theologica.